Análise do padrão de metilação das regiões line-1 de pacientes em primeiro episódio psicótico - Marques, Diogo Ferri [UNIFESP] (2018)
Schizophrenia is mainly characterized by psychosis (positive symptoms) such as delusions and hallucinations. The disorder may also involve negative symptoms (such as affective blunting), as well as cognitive impairment. The etiology of the disease is unclear, and the investigation of epigenetic mechanisms may be a pathway to better understand the pathophysiology and response to treatment of psychotic disorders. In the genome, repetitive regions, including the LINE1 (long interspersed nuclear element1) region, are susceptible to methylation of CpGs sites, and constitute a target for the evaluation of global methylation patterns, since they represent approximately 17% of human genome. Thus, the main hypothesis of this work would be that antipsychoticnaïve first episode psychosis (FEP) patients would have hypomethylation of the analyzed regions and, after risperidone treatment, the methylation patterns can be recovered in individuals who responded well to the drug. In addition, we anticipate finding an association of the clinical aspects of each patient with the applied psychiatric scales and the LINE1 methylation, so that we may in future use methylation levels as biological predictors of response. In this context, the present project aimed to evaluate the methylation of three LINE1 CpGs sites located in the 5'UTR promoter region in peripheral blood of 76 antipsychoticnaïve FEP patients and 62 healthy controls in order to understand the role of global methylation in the pathophysiology of schizophrenia. In addition, this project also aimed to evaluate possible changes in methylation related to treatment with risperidone (atypical antipsychotic) through a longitudinal study, following up these modifications in the patients for a period of two months. Recently, LINE1 has been a target of several studies related to neurodevelopment. Changes in its methylation are usually associated with genomic instability. To carry out the study, we started with blood samples collection from individuals and then with the DNA isolation followed by sodium bisulfite conversion. In this method, the DNA treated with bisulfite has the unmethylated cytosines converted into uracils whereas the methylated cytosines are not chemically modified and remain as cytosines. After conversion, the LINE1 (146 bp) fragments containing three CpGs are amplified using conventional PCR and subsequently sequenced using the pyrosequencing technique. Pyrosequencing consists of luminous signal registers by enzymatic reactions that generate peaks that are proportional to the number of nucleotides incorporated in the DNA strand. Finally, the step of methylation quantification was performed and then the methylation levels were compared among the groups. We found hypomethylation in FEP patients in all regions analyzed when compared to the control group, suggesting that LINE1 might be associated with the etiology of psychosis. After paired analysis to compare methylation before and after treatment, we observed that methylation means were higher after treatment with risperidone, although it was not statistically significant. Interestingly, we found a positive correlation in LINE1 CpG1 region and the response to the positive symptoms of FEP patients treated with risperidone, suggesting that nonresponders would have hypomethylation when compared to responders, which may be, in future, an important biological marker of prediction. This work brings new insights about the characterization of the methylation pattern of LINE1 CpGs sites in FEP patients, correlating methylation levels with clinical aspects.